Association of insulin resistance surrogates with live birth outcomes in women with polycystic ovary syndrome undergoing in vitro fertilization - Shenghao Wu; Yanhong Wu; Lizi Fang; Xiaosheng Lu (BMC Pregnancy and Childbirth)
Abstract Background Insulin resistance (IR) is a common pathophysiologic feature in patients with polycystic ovary syndrome (PCOS). However, there have been no studies investigating the association of IR surrogates with pregnancy outcomes in women with PCOS undergoing in vitro fertilization (IVF). Therefore, we explored the association between these factors among PCOS patients. Methods We conducted a retrospective study that included patients with PCOS who underwent IVF at a university-affiliated hospital. Blood samples and physical examinations are collected at reproductive center on fasting in the morning of the 2nd to 4th day of the menstrual cycle prior to medication. We categorized participants into “Non-IR group” (HOMA-IR < 2.2) and “IR group” (HOMA-IR ≥ 2.2). The association of IR surrogates [triglyceride-glucose-body mass index (TyG-BMI), triglyceride-glucose (TyG) and homeostasis model assessment (HOMA-IR)] with IVF outcomes was evaluated by regression model analysis. Moreover, we also performed sensitivity analyses with stratification and interaction tests. The primary outcome variable was the live birth rate. Results A total of 543 PCOS patients were finally included in the study. In all three regression models for the fresh embryo transfer (ET) cycles, all three IR surrogates showed stable negative correlations with live birth rate (in Model III: TyG-BMI OR = 0.99, 95% CI: 0.98 ~ 0.99; TyG OR = 0.47, 95% CI: 0.27 ~ 0.82; HOMA-IR OR = 0.84, 95% CI: 0.72 ~ 0.97; all P < 0.05), and this association was stable across all subgroups of the population (all P-interaction > 0.05). However, this relationship did not exist in frozen-thawed embryo transfer (FET) cycles. Furthermore, our study found that TyG-BMI was superior to TyG and HOMA-IR in predicting the rate of live birth in fresh ET cycles [TyG-BMI: 0.64 (95% CI: 0.58, 0.69) vs. TyG: 0.61 (95% CI: 0.55, 0.67) vs. HOMA-IR: 0.60 (95% CI: 0.55, 0.67)]. Conclusions Our study revealed that the three IR surrogates (TyG-BMI, TyG and HOMA-IR) were negatively associated with the live birth rates in fresh ET cycles. However, this relationship did not exist in FET cycles. Furthermore, our study found that TyG-BMI was superior to TyG and HOMA-IR in predicting the rate of live birth in fresh ET cycles.